Visibility and power in public opinion - Splichal, Slavko (Javnost-The Public, 2004)
The article discusses the relationship between the visible and clandestine executions of power, between the normative and instrumental visibility, and how the mechanisms of visibility and execution of power are embedded in public opinion processes. It is developed as a critique of those public opinion theories that are limited to their normative and repressive powers, and neglect concurrent dimensions of the execution of power. The critique is illustrated by results of a survey focused on the importance of the power of competence for public opinion.